Praktik State Censorship Terhadap Demokrasi Indonesia - Ningrat, Shinta Ressmy Cakra; Paskarina, Caroline; Rahmatunnisa, Mudiyati (International Journal of Demos (IJD), 2024)
AbstractDigital authoritarianism operates with various methods used by governments. What has been discovered in Indonesia in recent times is the use of censorship of freedom of expression carried out in the digital realm. This research tries to elaborate on these practices, starting from internet shutdowns and the formation of virtual police to repress citizens, to carrying out digital attacks on citizens. This research uses descriptive qualitative research methods using several theories and concepts, such as the concept of state censorship from Shadmer & Bernhardt, the concept of digital authoritarianism from Diprose and Power. This research proves that the findings of the practice of digital authoritarianism have a significant impact on the resilience, vulnerability and decline of Indonesian democracy. The government carries out the practice of digital authoritarianism through censorship to shape, control and manipulate citizens through cyberspace and is facilitated by communication technology.Key words: digital authoritarianism, internet shutdown, digital repressionÂ AbstrakOtoritarianisme digital berjalan dengan berbagai metode yang digunakan oleh pemerintah. Adapun yang sudah ditemukan di Indonesia dalam beberapa waktu terakhir adalah dengan menggunakan penyensoran kepada kebebasan berekspresi yang dilakukan di ranah digital. Penelitian ini mencoba mengelaborasi praktik-praktik tersebut, mulai dari internet shutdown dan pembentukan polisi virtual untuk merepresi warga negara, hingga melakukan serangan digital kepada warga negara. Penelitian ini mengenakan metode penelitian kualitatif deskriptif dengan menggunakan beberapa teori dan konsep, seperti konsep state censhorship dari Shadmer & Bernhardt konsep otoritarianisme digital dari Polyakova & Meserole (2019). Penelitian ini membuktikan temuan-temuan praktik otoritarianisme digital berdampak signifikan pada ketahanan, kerentanan dan kemunduran demokrasi Indonesia. Praktik otoritarianisme digital melalui penyensoran dilakukan pemerintah untuk membentuk, mengontrol dan memanipulasi warga negara melalui dunia siber dan difasilitasi oleh teknologi komunikasi.Kata kunci: otoritarianisme digital, internet shutdown, represi digital